2020
DOI: 10.3390/cancers12030747
|View full text |Cite
|
Sign up to set email alerts
|

Association between Angiotensin-Converting Enzyme Inhibitors and Lung Cancer—A Nationwide, Population-Based, Propensity Score-Matched Cohort Study

Abstract: Background: Direct evidence of lung cancer risk in Asian users of angiotensin-converting enzyme inhibitors (ACEIs) is lacking. Methods: The ACEI cohort comprised 22,384 patients aged ≥ 18 years with a first prescription of ACEI. The comparison angiotensin receptor blocker (ARB) cohort consisted of age-, sex-and comorbidity-matched patients at a ratio of 1:1. The primary outcome was the incidence of lung cancer, which was evaluated using a proportional hazard model. Results: The overall incidence rates of lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…The patients presented a wide range of demographic characteristics, which facilitated stratified analyses based on age, sex, and comorbidities, without losing precision, while avoiding bias from selection, nonresponse, or poor recall. The LHID has been shown to have appropriate levels of accuracy and completeness based on prescriptions and clinical diagnosis records [ 30 ]. In addition, we adjusted for numerous potentially confounding factors that are associated with T2DM over long observation periods.…”
Section: Discussionmentioning
confidence: 99%
“…The patients presented a wide range of demographic characteristics, which facilitated stratified analyses based on age, sex, and comorbidities, without losing precision, while avoiding bias from selection, nonresponse, or poor recall. The LHID has been shown to have appropriate levels of accuracy and completeness based on prescriptions and clinical diagnosis records [ 30 ]. In addition, we adjusted for numerous potentially confounding factors that are associated with T2DM over long observation periods.…”
Section: Discussionmentioning
confidence: 99%
“…These findings of the protective effect of ARBs on the risk of lung cancer are consistent with those of several previous studies. Observational studies and a meta-analysis reported an inverse association between ARB use and risk of lung cancer [10][11][12]14]. A cohort study using the Taiwan claims database reported a decreased risk of lung cancer of ARB users compared with ARB non-users (HR, 0.62; 95% CI, 0.53 to 0.73) [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of ARBs on lung cancer risk may vary depending on the reference medication. Cohort studies from the Taiwanese claims database also reported protective effects of ARBs on lung cancer [11,12]. However, these studies lacked important covariates including smoking status and were based on a user and nonuser study design, which could introduce a healthy user bias [13].…”
Section: Introductionmentioning
confidence: 99%
“…Higher quality research has gradually emerged in recent years. For example, Hicks et al con rmed that the long-term use of ACEIs for more than 5 years clearly promotes lung cancer [18,52]. The effects of ACEIs in tumor-bearing mice also differ across different tumor types, different tumor-bearing mouse models and different drug dosages.…”
Section: Discussionmentioning
confidence: 99%